2015
DOI: 10.1539/joh.14-0226-oa
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic exposure to arsenic induces apoptosis in the hippocampus of the mouse brains through the Bcl‐2/Bax pathway

Abstract: were found in the hippocampus of As-exposed mice. The expressions of the Bcl-2 gene and its protein in the hippocampus of As-exposed mice were significantly lower than those in the control group (p<0.05). However, the expressions of the Bax gene and its protein, and the expression ratio of Bax/Bcl-2 in the hippocampus were significantly higher in the groups exposed to As than in the control group (p<0.05). Moreover, the activity of caspase-3 in the hippocampus of mice exposed to As was higher than that in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 37 publications
3
20
1
Order By: Relevance
“…And changes in the expression ratio of Bax to Bcl‐2 might activate caspase‐3‐like protease in hippocampal neurons, leading to cell death (Tamatani, Ogawa, Nunez, & Tohyama, ). Bax and Bcl‐2 are significant members of the Bcl‐2 family, among which Bax could promote apoptosis and Bcl‐2 played an important role in preventing apoptosis (Wang et al, ). Apoptosis is triggered by high expression of Bcl‐2 in normal photoreceptors (Shinoura et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…And changes in the expression ratio of Bax to Bcl‐2 might activate caspase‐3‐like protease in hippocampal neurons, leading to cell death (Tamatani, Ogawa, Nunez, & Tohyama, ). Bax and Bcl‐2 are significant members of the Bcl‐2 family, among which Bax could promote apoptosis and Bcl‐2 played an important role in preventing apoptosis (Wang et al, ). Apoptosis is triggered by high expression of Bcl‐2 in normal photoreceptors (Shinoura et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…(b,d), The protein expressions of PTEN, p-Akt/Akt, Bcl-2/Bax, and cleaved caspase 3 in PC12 (b) and BV2 (d) cells in different transfection groups detected by western blot analysis; Different letters meant the significant difference, whereas same letters indicated no statistical significance. H/R: hypoxia/reoxygenation; miR: microRNA; NC: negative control; qRT-PCR: quantitative reverse-transcription polymerase chain reaction; si-PTEN: small interfering PTEN from mitochondria into the cytoplasm to induce cascades of cell apoptosis; meanwhile, Bax protein will bind to mitochondria to form mitochondria-Bcl-2 dimers, especially Bax oligomer, which further stimulates the release of cyt-c and eventually activating the expression of caspase 3(Ghosh, Das, Mandal, Dungdung, & Sarkar, 2010;Gogvadze, Robertson, Zhivotovsky, & Orrenius, 2001;Nicholls & Budd, 2000;Y. Wang et al, 2015).…”
mentioning
confidence: 99%
“…Proteins belonging to the Bcl‐2 family of proteins are regulators of apoptosis, and Bcl‐2 and Bax are representative proteins of this family. In theory, Bcl‐2 prevents apoptosis, while Bax plays a role in promoting apoptosis . In addition, the ratio of Bax/Bcl‐2 is believed to be a reliable indicator of apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…In theory, Bcl-2 prevents apoptosis, while Bax plays a role in promoting apoptosis. 37 In addition, the ratio of Bax/Bcl-2 is believed to be a reliable indicator of apoptosis. 38 Interestingly, a previous study showed that the knockdown of NLRP3 protects cells from apoptosis.…”
mentioning
confidence: 99%